Free Tissue Transfer in Patients with Hematologic Malignancies: A Case Series - Azmi Ritana; Dewi Aisiyah Mukarramah; Muhammad Irsyad Kiat; Kasih Rahardjo Djarot; Irena Sakura Rini; Resti Mulyasari; Oskar Ady Widarta (Indonesian Journal of Cancer, 2022)
Introduction: Free tissue transfer performed in patients with hematologic malignancies has several considerable challenges. Studies that report the challenges and outcomes related to these patients have been rather limited. This study presents the outcome of free tissue transfer as the reconstructive option for patients with hematologic malignancies. This study reports our experience regarding the perioperative evaluation, management, and outcomes of five patients with hematological malignancies that underwent free tissue transfer at Dharmais Cancer Hospital-National Cancer Center, Jakarta, Indonesia. Case Presentation: Five patients with hematologic malignancies, aged 26 to 60 years, who underwent free tissue transfer at Dharmais Cancer Hospital-National Cancer Center, Jakarta, Indonesia from January 2017 to February 2020 were included. The outcomes such as flap survival, complications, and mortality were reviewed. There were three patients with NonHodgkin lymphoma (NHL), one patient with peripheral T-cell lymphoma, and one patient with acute myeloid leukemia (AML). All patients received free tissue transfer with flap modalities such as radial free forearm flap and anterolateral thigh. One patient had a postoperative complication of vein compromise and was treated with negative pressure wound therapy (NPWT), which resulted in partial flap necrosis. Dehiscence was also found in one patient, and the patient underwent reoperation. Then, a myocutaneous trapezius flap was applied. There was no total flap loss, no donor site morbidity, and no mortality. Conclusions: This study has shown that free tissue transfer was a reliable reconstructive option for patients with hematologic malignancies. Flap survival and minimal complications can be achieved by optimizing the patient’s condition preoperatively, performing the meticulous nontraumatic surgical technique, closely monitoring potential post-operative complications, and implementing a multidisciplinary approach with the hematooncologists.